Anatomi Energi dan Daya Listrik untuk Pembelajaran Fisika Kelas XII di Sekolah Menengah Atas - Nuraini, Dalilah Jihan; Ramadhani, Amalia Efana Putri; Sari, Radita Nurnilam; Ernasari, Ernasari; Mahardika, I Ketut; Handono, Sri (Jurnal Ilmiah Wahana Pendidikan, 2024)
For the world of education, students must know how energy occurs and the types of energy. Therefore, good learning is needed which can be learned in schools. Science learning is material that provides knowledge of the natural surroundings that students must master, one of which is energy issues. The current physics learning media that is often used by schools is textbook-based learning media, posters and practical media. Like books, students have to read them and sometimes it's boring, while posters must have explanations, and practical media must have tools and guides. Looking at the existing learning media, there is a need for interactive learning media related to energy based on animation and audio and video explanations. This animation-based interactive learning media related to energy is built based on basic physics material at senior high school (SMA) level which focuses on basic learning about energy and types of energy. The interactive system built is an experiment with basic energy formulas which are input directly into the application with a multimedia-based learning concept. It is hoped that this animation-based application can be useful in understanding and recognizing basic energy physics, energy physics theory and the application of its formulas by utilizing science learning applications by means of independent